Peran Muhammadiyah dalam Pengembangan Kewirausahaan di Kota Tangerang - Meisari, Yola Dyfa; Abdullah, Faisal (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
This research highlights Muhammadiyah's strategic role in developing entrepreneurship in Tangerang City, which is a center of economic potential with more than 11,000 MSMEs. As a social and religious organization, Muhammadiyah is committed to increasing the economic capacity of the community through various programs such as the Muhammadiyah Trade Center and business training. The emphasis on Islamic values ​​in business activities is also a characteristic, where justice and social responsibility are prioritized. Despite challenges such as limited economic education and access to capital, digitalization efforts offer solutions to these difficulties. Overall, Muhammadiyah has the potential to become the main driver of economic progress and community empowerment in Indonesia.   Abstrak Penelitian ini menyoroti peran strategis Muhammadiyah dalam pengembangan kewirausahaan di Kota Tangerang, yang merupakan pusat potensi ekonomi dengan lebih dari 11.000 UMKM. Sebagai organisasi sosial dan keagamaan, Muhammadiyah berkomitmen untuk meningkatkan kapasitas ekonomi masyarakat melalui berbagai program seperti Muhammadiyah Trade Center dan pelatihan bisnis. Penekanan pada nilai-nilai Islam dalam kegiatan usaha juga menjadi ciri khas, di mana keadilan dan tanggung jawab sosial diutamakan. Meskipun menghadapi tantangan seperti keterbatasan pendidikan ekonomi dan akses modal, upaya digitalisasi menawarkan solusi untuk kesulitan ini. Secara keseluruhan, Muhammadiyah berpotensi menjadi penggerak utama kemajuan ekonomi dan pemberdayaan masyarakat di Indonesia.